Merozoite antigens of Plasmodium falciparum elicit strain-transcending opsonizing immunity - Hill, D; Wilson, D; Sampaio, N; Eriksson, E; Ryg-Cornejo, V; Harrison, G; Uboldi, A; Robinson, L; Beeson, J; Siba, P; Cowman, A; Hansen, D; et al. (American Society for Microbiology, 2016)
It is unclear whether naturally acquired immunity to Plasmodium falciparum results from the acquisition of antibodies to multiple, diverse antigens or to fewer, highly conserved antigens. Moreover, the specific antibody functions required for malaria immunity are unknown, and hence informative immunological assays are urgently needed to address these knowledge gaps and guide vaccine development. In this study, we investigated whether merozoite-opsonizing antibodies are associated with protection from malaria in a strain-specific or strain-transcending manner by using a novel field isolate and an immune plasmamatched cohort from Papua New Guinea with our validated assay of merozoite phagocytosis. Highly correlated opsonization responses were observed across the 15 parasite strains tested, as were strong associations with protection (composite phagocytosis score across all strains in children uninfected at baseline: hazard ratio of 0.15, 95% confidence interval of 0.04 to 0.63). Opsonizing antibodies had a strong strain-transcending component, and the opsonization of transgenic parasites deficient for MSP3, MSP6, MSPDBL1, or P. falciparum MSP1-19 (PfMSP1-19) was similar to that of wild-type parasites. We have provided the first evidence that merozoite opsonization is predominantly strain transcending, and the highly consistent associations with protection against diverse parasite strains strongly supports the use of merozoite opsonization as a correlate of immunity for field studies and vaccine trials. These results demonstrate that conserved domains within merozoite antigens targeted by opsonization generate strain-transcending immune responses and represent promising vaccine candidates.